Determinants of participation in contract farming in pig production in Northern Vietnam - Costales, A.; Son, N.T.; Lapar, Ma. Lucila; Tiongco, Marites M. (Food and Agriculture Organization of the United Nations, 2008)
The rapid growth in demand for pork in Viet Nam presents an opportunity for rural households raising pigs to improve their incomes. This market potential could be exploited to improve incomes of rural smallholders through institutional arrangements that provide improved access to livestock markets and services, through formal and informal contract arrangements. Contract arrangements, however, have explicit and implicit barriers to entry that tend to exclude smallholders, depending on the nature of the contracts. Based on data from a field survey conducted in four provinces in Northern Viet Nam in 2005-06, comprising a sample of 400 pig raising households (200 independent producers, 166 farmers with informal contracts, and 34 farmers with formal contracts with a large integrator), a multinomial logit model was used to identify the factors that determine the likelihood of engagement in formal or informal contracts. A simple probit model was subsequently developed for the determinants of engagement in informal contract arrangements. Results indicate that farmers with higher levels of education and larger physical asset holdings are more likely to be engaged in formal contracts. The latter are largely limited to large-scale farmers (with mean holdings of about 600 pigs per farm) that specialized in pig fattening. In contrast, informal contracts are less exclusionary of smallholder producers. Households with higher levels of education, managing full-cycle pig operations, and with pig production being a main occupation, are more likely to engage in informal contracts, than remain independent producers. However, rather than size of physical assets, social capital appears to be a more important determinant of engaging in informal contracts. Providing a supportive policy and institutional environment for various informal contracting arrangements in pig production and marketing could improve access to markets and services by rural smallholder pig producers.